Catalase enzymatic activity in adult mosquitoes (Diptera: Culicidae): taxonomic distribution of the continuous trait suggests its relevance for phylogeny research - Razygraev, Alexey V. (Zootaxa, 2023)
Molecular research based on gene sequence analysis and performed for decades, in general, supported morphology-based groupings of the species within the family Culicidae, but phylogenetic relationships between some genera and tribes remained uncertain for a long time. Interspecific differences in catalase, an antioxidant enzyme important for maintaining prolonged lifespan and reproduction, have not been studied extensively by estimating enzymatic activity levels. Here, catalase enzymatic activity was assayed in extracts of male mosquitoes belonging to 10 species of the subfamily Culicinae, including species from tribes of disputable phylogeny. Three species of Chaoboridae (nearest outgroup taxon) and mosquitoes from the subfamily Anophelinae (one species complex) were also added to the study. At least in Culicinae, immature adult males (less than one day after emergence) have distinctly elevated specific activity of catalase; therefore, only mature males of all species were used for the comparative study. As a result, significant differences in catalase activity were revealed between tribes, genera and particular species. Among culicids, the genera Coquillettidia and Culiseta were found to include the species with the highest and relatively high catalase activity, which is consistent with the affinity of the tribes Mansoniini and Culisetini to each other. Within Ochlerotatus, extremely low catalase activity in Oc. hexodontus suggests the more distant position of this species from Oc. cantans (Meigen) and Oc. communis (de Geer) than the positions of the latter two species from each other. Additional study of catalase activity in overwintering females of the genus Culex revealed significantly higher enzyme activity in Cx. torrentium in comparison with Cx. pipiens, which supports their quite distant positions from each other within the genus. Considering the distribution of catalase activity within the tree obtained, the preliminary outcome is that Culiseta retains the elevated level of catalase activity that was lost during the early separation of Anopheles and subsequent separation of Culex and Aedes/Ochlerotatus after Anopheles from their common branch with Culiseta/Coquillettidia. Overall, the use of taxonomic distribution of catalase activity levels appears to be effective for resolving disputed events of mosquito phylogeny.